Review: Peningkatan Produktivitas Tebu (Saccarum Officinarum l.) pada Lahan Kering Melalui Pemanfaatan Bahan Organik dan Bahan Pelembab Tanah Sintesis - Edi Tando (Biotropika: Journal of Tropical Biology, 2017)
Sugar cane (Saccarum officinarum L.) is a crop that can only be planted in the tropics and having high economic value . The main problems sugar industry in indonesia is low sugar price because of frequent imports sugar, due to technical the low agronomy not done with perfect. The development of sugar cane dry land an option pledged to speed up the process of the quantity , quality , and continuity sugar confection to independence national sugar. The purpose of drafting this paper is to provide information about increased productivity sugar cane in dry land through the application of organic matter and moisturizing synthesis of land ( poliakrilamides ). The role of organic matter very large in boost fertility physical, biology and chemistry the ground and determine productivity land. Organic material has had several excellence namely materials readily obtainable , cheap. But supply always changing and it should be given many times and in large quantitie. Besides organic matter, in agriculture has recommended poliakrilamide as a humectant land can improve the nature of fisikokimia land, reduce the number of irrigation, lost the confusion and production costs plant. The use of poliakrilamide is one of the most effective technology and economical latest identified to finish improve the quality of water required